Khôi phục phần dữ liệu bị mất trong ảnh động - Nguyễn Đăng Quang (Journal of Technical Education Science, 2006)
Making use of PDE in digital image processing has been widely developed recently. First introduced by Bertalmio, digital image inpainting algorithms did give impressive results in removing scratches in old images. This paper is dedicated to briefly present achieved works has been made to apply this technique in removing blotches and scratches in old films.